STRATEGI PEMASARAN BERBASIS RELATIONSHIP MARKETING UNTUK MENINGKATKAN RETENSI PELANGGAN - Risdwiyanto, Andriya; Arief, Zaenal; Artino, Adi; Nuraini, Luthfi; Afridhianika, Annisa Nugraheni (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the effectiveness of relationship marketing strategies in increasing customer retention. This research approach collects data through a literature review, which involves reading literature from various sources including books, articles, journals, and reports using qualitative and deductive approaches. The results of this study indicate that a relationship marketing-based marketing strategy emphasizes building long-term relationships between companies and customers as an effort to increase customer retention. The strategies implemented include personalized service, regular and consistent communication, providing loyalty programs, handling complaints quickly and with solutions, providing appreciation to loyal customers, and involving customers in product or service development. These strategies aim to increase customer satisfaction, trust, and emotional attachment to the company. The implementation of an integrated relationship marketing-based marketing strategy has been proven to play a significant role in strengthening customer loyalty and encouraging the sustainability of long-term business relationships.